Increasing resilience and security of supply production post-COVID-19: from global to regional value chains? Case studies on medical and pharmaceutical products - Jan Grumiller; Hannes Grohs; Christian Reiner (Austrian Foundation for Development Research (ÖFSE), 2021)
The COVID-19 pandemic has exposed the fragility of medical product and pharmaceutical global value chains (GVCs). Against this background, debates on various policies to increase the resilience of these supply chains intensified. However, there is currently no consensus on which policies are required to ensure supply security for 'critical' or 'essential' products in the European Union (EU), and even the definition of these products is the subject of a debate. This report presents a detailed analysis of the medical products and pharmaceutical GVCs in order to foster our understanding of their vulnerabilities and to identify potentials for increasing their resilience. Given the large diversity of products within the medical and pharmaceutical sectors, the report presents a selection of three case studies on representative products for each of the two sectors/GVCs: (i) respirators, (ii) examination gloves and (iii) ventilators for medical products, and (a) penicillin (antibiotic), (b) paracetamol (analgesic), and (c) heparin (anticoagulant) for pharmaceuticals. The effects of COVID-19 on medical and pharmaceutical GVCs were distinct: most countries in the EU faced shortages of various critical medical products in early 2020, with negative effects on patients and health care workers. In contrast, COVID-19 induced shortages of pharmaceutical products were, so far and with a few exceptions, rare and with very limited negative effects for patients. Having said that, the COVID-19 pandemic highlighted already existing and potential new vulnerabilities for various pharmaceutical products in the EU. – – Die COVID-19-Pandemie hat die Anfälligkeit globaler Wertschöpfungsketten (GVCs) für Medizinprodukte und Pharmazeutika offengelegt. Vor diesem Hintergrund haben sich die Debatten über verschiedene wirtschaftspolitische Maßnahmen zur Erhöhung der Resilienz von Lieferketten intensiviert. Allerdings herrscht aktuell keine Einigkeit darüber, welche Maßnahmen zur Gewährleistung der Versorgungssicherheit für 'kritische' oder 'essenzielle' Produkte in der Europäischen Union (EU) erforderlich sind, und selbst die Definition dieser Produkte ist Gegenstand der Diskussion. Der vorliegende Report präsentiert eine detaillierte Analyse der GVCs medizinischer und pharmazeutischer Produkte mit dem Ziel ein besseres Verständnis für ihre Vulnerabilitäten zu schaffen und so Potenziale zur Erhöhung ihrer Resilienz zu identifizieren. Angesichts der großen Produktvielfalt innerhalb des Medizin- und Pharmasektors präsentiert der Report drei Fallstudien zu repräsentativen Produkten für jeden der beiden Sektoren bzw. GVCs: (i) Beatmungsgeräte, (ii) medizinische Handschuhe und (iii) Beatmungsgeräte für medizinische Produkte und (a) Penicillin (Antibiotikum), (b) Paracetamol (Analgetikum) und (c) Heparin (Antikoagulans) für pharmazeutische Produkte. Der Schwerpunkt der Analyse der medizinischen und pharmazeutischen GVCs unterscheidet sich, da sich die COVID-19-Pandemie auf die Produkte unterschiedlich auswirkte: Die meisten Länder in der EU waren Anfang 2020 mit Engpässen bei verschiedenen kritischen medizinischen Produkten konfrontiert. Dies hat zu negativen Auswirkungen auf PatientInnen und MitarbeiterInnen des Gesundheitswesens geführt. Im Gegensatz dazu waren COVID-19-induzierte Engpässe bei pharmazeutischen Produkten bisher - mit einigen wenigen Ausnahmen - selten und mit sehr begrenzten negativen Auswirkungen für PatientInnen. Die COVID-19-Pandemie hat jedoch bereits bestehende sowie potenzielle Vulnerabilitäten für verschiedene pharmazeutische Lieferketten in der EU aufgezeigt.
Keywords: 330; Coronavirus; Epidemie; Medizinprodukt; Arzneimittel; Globale Wertschöpfungskette; Coping-Strategie; EU-Staaten